Challenges and Strategies for Early Childhood Special Education Services in Florida's Rural Schools: A DELPHI Study - Keith E. Weiss; Vivian I. Correa (Journal of Research in Rural Education, 1996)
In this study, we asked early childhood special educators and administrators in rural areas to provide insight into educational issues in rural Florida school districts. The Delphi technique used in this investigation incorporated two rounds ofquestionnaires to generate responses and develop agreementfrom a panel ofrural service providers. The panel was asked to (a) identify the problems facing rural educational service providers that hinder their ability to serve the needs ofchildren 3 to 5 years ofage with disabilities and (b) determine the modifications in current service programs that would help improve the delivery ofservices to these children.